2011
DOI: 10.3342/ceo.2011.4.1.11
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine and N-Nitroarginine Methyl Ester Attenuate Carboplatin-Induced Ototoxicity in Dissociated Spiral Ganglion Neuron Cultures

Abstract: ObjectivesCarboplatin, a platinum-containing anti-cancer drug used to treat a variety of cancers, induces ototoxicity. Since, reactive oxygen species (ROS) and nitric oxide (NO) seem to be responsible for this toxicity, the antioxidant, N-acetyl-L-cysteine (L-NAC), and NO synthetase inhibitor, N-nitro-L-arginine methyl ester (L-NAME) were predicted to have protective effects against carboplatin ototoxicity. The aim of this study was to test for the protective effects of L-NAC and L-NAME on cochlear hair cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In addition, outer hair cells were clearly damaged more than inner hair cells (Fig. 3), consistent with previous in vivo and in vitro studies in rats [31, 34, 76–78] .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, outer hair cells were clearly damaged more than inner hair cells (Fig. 3), consistent with previous in vivo and in vitro studies in rats [31, 34, 76–78] .…”
Section: Resultssupporting
confidence: 91%
“…The in vitro ototoxic effects of carboplatin have been studied in very few species using as cell lines and cochlear cultures [30, 76–78] . According to the very limited discoveries from previous studies in the rat cochlear culture system, carboplatin absolutely selectively destroys outer hair cells and spiral ganglion neurons in the postnatal day 3 rat cochlear explant [76–78] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is reported that CBP-induced cardiotoxicity is related to ROS production in mice and could be prevented by using pravastatin, which protected against oxidative stress [32]. Production of ROS is involved in CBP-induced damage to murine cochlear hair cells and spiral ganglion neurons, and can be attenuated by the antioxidant NAC [49].…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that myelotoxicity of CBDCA may be caused by the free radicals mediated assault to DNA in murine bone marrow cells because (i) CBDCA induced free radicals are reported to be responsible for neurotoxicity, ototoxicity 29 and nephrotoxicity 3 , (ii) heavy metals are known to generate free radicals which can interact with DNA and produce lesions 30 and (iii) CBDCA can intercalate within DNA that resulted in the formation of the free radicals generated by platinum can damage DNA in spite of their short lifespan. We examined this hypothesis by measuring cellular oxidative and nitrosative stress.…”
Section: Discussionmentioning
confidence: 99%